Evaluation of the role of local therapy in patients with cN1M0 prostate cancer: A population-based study from the SEER database - Qi, Feng; Xu, Wenbo; Li, Lu; Li, Xiao; Xu, Zicheng (Frontiers in Oncology, 2022)
Objective To investigate the prognostic value of local therapy (LT) in cN1M0 prostate cancer (PCa). Methods Patients diagnosed with cN1M0 PCa were extracted from the surveillance, epidemiology, and end results (SEER) database. Kaplan-Meier (KM) curve was used to compare the survival outcomes between patients treated with and without LT. Further, among patients receiving LT, KM analysis was also applied to investigate the survival differences in patients with radical prostatectomy (RP) and radiation therapy (RT). Propensity score matching (PSM) analysis was performed to balance the basic characteristics of patients in each group and make it comparable when exploring the survival impact of different treatment types. Finally, uni- and multivariable Cox proportional-hazards models were utilized to identify independent prognostic factors associated with overall survival (OS) and cancer-specific survival (CSS) in this population. Results Patients treated with LT had significantly better OS (P<0.0001) and CSS (P<0.0001) than those without LT, as well as in most subgroups, except for non-White patients, or those with ISUP grade group 1 or T3 stage. Notably, patients receiving RP also had significantly better OS (P=0.00012) and CSS (P=0.0045) than those treated with RT alone, especially in those aged ≥75 years old, prostate-specific antigen (PSA) 10-20 ng/mL, ISUP grade 1-3 or non-white patients. Finally, clinical T stage, ISUP grade group and the administration of LT were identified to be independent prognostic factors for OS and CSS among cN1M0 PCa patients. Conclusion The cN1M0 PCa patients treated with LT were associated with significantly better survival. Among patients receiving LT, the combination of RP and PLND could lead to a better prognosis compared to RT alone in most subgroups. An individualized treatment strategy is warranted to be developed after weighing the benefits and risks of treatment.